Animal personality in a foundation species drives community divergence and collapse in the wild. (22nd July 2015) - Pruitt, Jonathan N.; Modlmeier, Andreas P.; Quinn, John
Summary Despite thousands of papers on the topic, precious few of the studies on animal personality have considered the role of personality in shaping community‐level processes. Here, we test the effect of individual variation on the long‐term trajectories of biological communities, from initiation to their demise. The spider Anelosimus studiosus builds webs that serve as habitat for >50 species of spider, which together construct a species‐rich silken reef. This species also exhibits a temporally consistent behavioural polymorphism where females exhibit either an aggressive or docile phenotype (personality). In this study, we established incipient colonies of either two docile or two aggressive females and then tracked community succession and persistence over 7 years in the field. In particular, we noted the community compositions associated with colony extinction/collapse events, which are common in this species. The community composition of webs founded by different phenotypes diverged rapidly in their early successional stages. However, this period of divergence was ephemeral and all communities eventually converged on a similar composition; communities founded by aggressive females merely took longer to reach it. This secondary stage of community convergence was itself short‐lived and independent of founders' personality; all communities collapsed within a year of achieving it. Experimentally imposing this fatal climax composition on colonies caused 80% of communities to collapse within a year, suggesting that this climax composition actually causes the collapse of the community. Community collapse was characterized by a complete die‐off of the foundation species and the dispersal of all other spiders. Thus, the behavioural traits of the founding, foundational individuals of these communities dictate their path of succession and longevity in the wild.